Determinan Peluang Kelayakan Pembiayaan Perusahaan Sektor Perdagangan Besar dan Eceran di Indeks Saham Syariah Indonesia - Rista Agustiani; Tjetjep Djuwarsa (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study tries to assess the feasibility opportunities of the company’s financing and to detect early the company’s capability and willingness to pay their debts which is proxied by solvency ratios, and aims to predict factors that can affect the financing feasibility opportunities using independent variables. Some of the independent variables proposed respectively are Current Ratio (CR), Total Asset Turn Over (TATO), Sharia Compliance represented by Interest-based Debt to Total Asset Ratio, and inflation as a macroeconomic factor. The research model is quantitative with a research sample from 25 wholesale and retail trade sector companies listed in Indonesian Sharia Stock Index period 2013-2018. The results of this study conclude that Current Ratio (CR) and Interest-based Debt to Total Asset ratio (IDtTA) affect the company’s financing feasibility opportunities. Meanwhile, Total Asset Turn Over (TATO) and inflation do not affect on the company’s financing feasibility opportunities. The data analysis technique used Principal Component Analysis and logistic regression technique with a predictive accuracy rate of 85,33%.